An audit of immunofixation requesting practices at a South African referral laboratory - Verena Gounden; Yashna Rampursat (AOSIS, 2014)
Background: It is common practice in most chemical pathology laboratories for reflective immunofixation electrophoresis (IFE) to occur following the detection or suspicion of a paraprotein on serum protein electrophoresis (SPEP). The chemical pathology laboratory at Inkosi Albert Luthuli Central Hospital (IALCH) in Durban, South Africa, is currently the only non-private laboratory in the KwaZulu Natal province that performs SPEP analysis, with current practice requiring that the clinician request IFE following suggestion by the laboratory after a suspicious SPEP result. Objectives: To review the current process for IFE at IALCH in the context of reflective testing and to examine the use of the alpha-2-globulin/alpha-1-globulin ratio as a predictor of a positive IFE result. Methods: Data for 1260 consecutive SPEP tests performed at the IALCH National Health Laboratory Service were collected between February and July 2011. SPEP and IFE were performed with a Sebia Hydrasys automated electrophoresis system. The alpha-2-globulin/alpha-1-globulin ratio was calculated using density of corresponding fractions on SPEP. Results: Analysis revealed that of the 1260 SPEPs performed during the analysis period, 304 IFEs were suggested by the reviewing pathologist. A total of 45 (15%) of the suggested IFEs were subsequently requested by the attending clinicians. Almost half (46.5%) (n = 20) of the suggested IFEs that were performed revealed the presence of a paraprotein. There was no statistically-significant difference between the alpha-2-globulin/alpha-1-globulin ratio for patients with positive or negative IFEs (p-value = 0.2). Conclusions: This study reveals the need for reflective addition of IFE testing by the laboratory following suspicious findings on SPEP.